2014
DOI: 10.3390/v6052204
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Quantitative Detection Method for Viral Hemorrhagic Septicemia Virus (VHSV) Genogroup IVa

Abstract: Viral hemorrhagic septicemia virus (VHSV) is a problematic pathogen in olive flounder (Paralichthys olivaceus) aquaculture farms in Korea. Thus, it is necessary to develop a rapid and accurate diagnostic method to detect this virus. We developed a quantitative RT-PCR (qRT-PCR) method based on the nucleocapsid (N) gene sequence of Korean VHSV isolate (Genogroup IVa). The slope and R2 values of the primer set developed in this study were −0.2928 (96% efficiency) and 0.9979, respectively. Its comparison with vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Research on other virus types suggests that the number of virus copies and TCID 50 are comparable. 45 However, it would be important to confirm this for SARS-CoV-2. Third, for breath and cough microdroplets release, we used data collected in experimental setups involving healthy young participants.…”
Section: Limitationsmentioning
confidence: 99%
“…Research on other virus types suggests that the number of virus copies and TCID 50 are comparable. 45 However, it would be important to confirm this for SARS-CoV-2. Third, for breath and cough microdroplets release, we used data collected in experimental setups involving healthy young participants.…”
Section: Limitationsmentioning
confidence: 99%
“…Based on geographic location and genomic sequence similarities, VHSV was partitioned for four groups (I-IV) and several subgroups (IVa, IVb and IVc) (Einer-jensen et al, 2004). Here, the phylogenetic analysis based on the whole-genome sequences and G gene sequences revealed that the VHSVLB2018 isolate belonged to genotype IVa, which is similar to the VHSV isolates from other fishes in Asia (Kim et al, 2014). Differently, a VHSV isolate of genotype IVb was detected from largemouth bass in the great lakes region in the United States and Canada (Kim & Faisal, 2011;Throckmorton et al, 2017).…”
Section: Discussionmentioning
confidence: 75%
“…Since the first VHSV strain was isolated from farmed Japanese flounder in Japan (Takano, Nishizawa, Arimoto, & Muroga, ), many different strains of VHSV have been reported in a wide range of fish species in Asia. Almost all Asia isolates of VHSV were classified into genotype IVa (Ahmadivand et al, ; Kim et al, ). It is well known that VHSV can be transferred by contaminated water and fish‐to‐fish contact; thus, VHSVLB2018 probably originated from other VHSV isolates in Asia through horizontal transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) We used information about virus copies but compare the results with TCID 50 infective dose. Research on other virus types suggests that the number of virus copies and TCID 50 are comparable 45 . However, it would be important to confirm this relationship for the case of SARS-CoV-2.…”
Section: Limitationsmentioning
confidence: 99%